POTRET BUMDES KECAMTAN AIR SUGIHAN dan KECAMATAN AIR KUMBANG KABUPATEN BANYUASIN - Sunardi Sunardi; Diah Isnaini Asiati; Apriyanto Apriyanto (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Improving Bumdes governance will always require identification of problems and solutions so that Bumdes can go to star 5. This activity carried out in 38 villages in Air Kumbang and Muara Sugihan districts, participants of each event by two Bumdes managers, the activities are divided into two days. Different, by collaborating with the sub-district government and Palembang Muhammadiyah University. The result of this activity is Bumdes has many internal problems. Furthermore, the solutions that must be immediately adopted are: fixing and strengthening, business mapping, and business selection evaluated through a business feasibility study, an evaluation of the AD / ART that has prepared, the need for a companion from the government, and universities and strengthening human resources.